SKRINING KIA SECARA ONLINE UNTUK MENDETEKSI FAKTOR RESIKO KEHAMILAN - Khulul Azmi; Ariana; Aisyah; Annisa Hardina (Jurnal Inovasi dan Terapan Pengabdian Masyarakat, 2021)
Background: Pregnancy for a woman is both happy and anxious. Feelings of fear and anxiety about bad things that can happen to him, especially during childbirth. Coping with childbirth is one of the factors that can cause anxiety. The health of pregnant women in the era of the Covid-19 pandemic must be a priority scale for the medical world today. (Mustika, 2020). During the time of the corona or Covid-19 pandemic, which is increasingly spreading in Indonesia, pregnant women should postpone consultations at health facilities, both clinics and hospitals. Preventing Covid-19 is certainly a shared responsibility, especially for pregnant women who are vulnerable and often worry about the condition of the fetus. Methods: To achieve the goals that have been previously formulated, this community service implementation is carried out in several steps involving field research methods. Result: From the results of this service, the output obtained was an online screening which can be accessed through: https://skriningkia.com/ Conclusion: This activity is carried out to introduce technology in order to improve maternal and child health. Utilizing online media to expand reach and detect emergencies